New polyunsaturated fatty acid amides isolated from the seeds of Zanthoxylum piperitum - Jang, Kyoung Hwa; Chang, Yong Ha; Kim, Dae-Duk; Oh, Ki-Bong; Oh, Uhtaek; Shin, Jongheon (Archives of pharmacal research, 2008)
Five linear fatty acid amides ( 1–5 ) of the sandshool class, including two new compounds, were isolated from Zanthoxylum piperitum seeds. Based on combined spectral analyses, the structures of new compounds 4 and 5 were determined to be 2′,3′-dihydroxy-α-sanshool and 2′,3′-dihydroxy-β-sanshool, respectively. These compounds exhibited weak cytotoxicity in the A-549 (human lung cancer) cell line.